2021
DOI: 10.1101/2021.07.09.451762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental evolution ofBacillus subtilisonArabidopsis thalianaroots reveals fast adaptation and improved root colonization in the presence of soil microbes

Abstract: The soil ubiquitous Bacillus subtilis is known to promote plant growth and protect plants against disease. These characteristics make B. subtilis highly relevant in an agricultural perspective, fueling the interest in studying B. subtilis-plant interactions. Here, we employ an experimental evolution approach to explore adaptation of B. subtilis to Arabidopsis thaliana roots. B. subtilis rapidly adapts to the plant root environment, as evidenced by improved root colonizers observed already after 12 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 96 publications
(215 reference statements)
2
7
2
Order By: Relevance
“…Similar to the present research, altered bacterial motility of evolved isolates during adaptation was reported in an evolution experiment involving the gram-positive rhizobacterium, B. subtilis DK1042 (DK1042) (Nordgaard et al, 2021). DK1042 rapidly adapted to Arabidopsis following 12 consecutive transfers from seedling to seedling in a hydroponic system.…”
Section: Adaptative Mechanisms Of Root-colonizing Microbessupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to the present research, altered bacterial motility of evolved isolates during adaptation was reported in an evolution experiment involving the gram-positive rhizobacterium, B. subtilis DK1042 (DK1042) (Nordgaard et al, 2021). DK1042 rapidly adapted to Arabidopsis following 12 consecutive transfers from seedling to seedling in a hydroponic system.…”
Section: Adaptative Mechanisms Of Root-colonizing Microbessupporting
confidence: 83%
“…Evolved DK1042 isolates displayed increased rootcolonization ability, which was associated with robust biofilm formation in response to the plant polysaccharide xylan. Surprisingly, in contrast with the Pseudomonas mutants from the present study, DK1042 mutants were significantly impaired in both swimming and swarming motility (Nordgaard et al, 2021). In another experimental evolutionary study involving Bacillus thuringiensis 407 Cry -(Bt407) and Arabidopsis, and using the same hydroponic setup as described by Nordgaard et al (2021) but performed over 40 cycles, led to the emergence of isolates with reduced swimming and enhanced swarming motility in two out of five lineages (Lin et al, 2021).…”
Section: Adaptative Mechanisms Of Root-colonizing Microbescontrasting
confidence: 58%
“…4 ) [ 30 ]. Directed laboratory evolution of Bacillus root colonizers in planta has additionally provided a robust methodology for studying root-associated biofilms and the evolutionary path connected to this colonization setup [ 30 , 107 , 108 ]. This approach allowed the identification of several genes related to efficient root colonization by B. cereus .…”
Section: Ecological Importance Of B Cereus Biofilmsmentioning
confidence: 99%
“…Subsequently, seedlings were soaked on a P5_B1gfp bacterial solution (OD600 = 0.1) for 10 minutes and placed in LEGO brick boxes containing 50 g of beads (35). The root colonization was tracked by confocal laser scanning microscopy imaging (CLSM) as described previously (15,(36)(37)(38)(39). Colonized roots were washed twice with sterile ddH2O and placed onto microscope slides.…”
Section: Root Colonization Assaymentioning
confidence: 99%